The influence of tympanic membrane perforation site on the hearing level of conductive hearing loss in chronic suppurative otitis media - Adhika Banu Wicaksono; Edhie Samodra; Melysa Fitriana; Feri Trihandoko; Anisa Haqul Khoiria; Dyah Ayu Kartika Dewanti (Universitas Gadjah Mada, 2022)
Chronic suppurative otitis media (CSOM) is an infection of the middle ear cavity both partially and totally. It is characterized by ear discharge through a tympanic membrane perforation for over a period of 2 to 6 weeks. Hearing loss is the most common complication of CSOM. One of the degrees of hearing loss in tympanic membrane perforation is depending on the site of perforation, but this premise is still debatable because of pros and contras by some researchers. This study aimed to assess the degree of hearing loss in relation to the site of tympanic membrane perforation. A cross-sectional prospective study design was performed involving 43 patients of safe type CSOM who came to the Department of Otolaryngology Head and Neck Surgery from the period January 2016 to November 2018. All subjects were divided into 4 groups based on the site of perforation. There was a perforation in the posteroinferior, the posterosuperior, the anteroinferior, and the anterosuperior. A statistical analysis using Anova along with multivariate analysis was conducted. Our result showed that the most common site of tympanic membrane perforation was at the anteroinferior (30 samples, 59.8%). The highest hearing threshold was seen at posteroinferior with a mean hearing level of 37.7±2.0 dB, anteroinferior with a mean hearing level of 31.7±0.7 dB, anterosuperior with a mean hearing level 30.7±1.4 dB, and posterosuperior mean hearing level 28.9±1.5 dB. The difference was found significant with p=0.004. Posteroinferior tympanic membrane perforation had a higher number of hearing loss compared to the other sites. In conclusion, the tympanic membrane perforation site has an important role in the hearing level of conductive hearing loss in CSOM.